Constitutional Question dan Constitutional Complaint: Pembaharuan Mahkamah Konstitusi dan Terjaminnya Hak Konstitusional Warga Negara - Tegar Raffi Putra Jumantoro; Syedna Ahmad Albanna; Antikowati Antikowati; Igam Arya Wada (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The constitutional rights of citizens are the main rights that should be protected and guaranteed by the state. However, in practice, there are still several violations of the constitutional rights of citizens in Indonesia, for example in the process of making legal products, namely laws and regulations, which do not include participation from citizens and the increasingly narrowing of citizens' right to freedom in expressing their suggestions and input in public. . Seeing the problems above, researchers try to provide recommendations by internalizing adjudicating Constitutional Question and Constitutional Complaint cases as one of the powers of the Constitutional Court. This research is very important as a basis for state officials in guaranteeing the constitutional rights of citizens in the future. This research uses normative legal methods and a statutory approach. The data collection method was carried out using library research. The results of the research found legal facts that the concepts of Constitutional Question and Constitutional Complaint had not yet been adopted as part of the authority of the Constitutional Court and found several dynamics of violations of citizens' constitutional rights. In practice, the Constitutional Court only has the authority to hear and decide cases where the applicant feels disadvantaged by the existence of the law, not by state officials. Researchers recommend synergies in increasing the accessibility of public services for handling Constitutional Court cases online as well as the implementation of adjudicating Constitutional Question and Constitutional Complaint cases in Indonesia.